Α-Conotoxin Vc1.1 inhibits human dorsal root ganglion neuroexcitability and mouse colonic nociception via GABAB receptors. Issue 6 (17th February 2016) - Castro, Joel; Harrington, Andrea M; Garcia-Caraballo, Sonia; Maddern, Jessica; Grundy, Luke; Zhang, Jingming; Page, Guy; Miller, Paul E; Craik, David J; Adams, David J; Brierley, Stuart M
Abstract : Objective: α-Conotoxin Vc1.1 is a small disulfide-bonded peptide from the venom of the marine cone snail Conus victoriae . Vc1.1 has antinociceptive actions in animal models of neuropathic pain, but its applicability to inhibiting human dorsal root ganglion (DRG) neuroexcitability and reducing chronic visceral pain (CVP) is unknown. Design: We determined the inhibitory actions of Vc1.1 on human DRG neurons and on mouse colonic sensory afferents in healthy and chronic visceral hypersensitivity (CVH) states. In mice, visceral nociception was assessed by neuronal activation within the spinal cord in response to noxious colorectal distension (CRD). Quantitative-reverse-transcription-PCR, single-cell-reverse-transcription-PCR and immunohistochemistry determined γ-aminobutyric acid receptor B (GABAB R) and voltage-gated calcium channel (CaV 2.2, CaV 2.3) expression in human and mouse DRG neurons. Results: Vc1.1 reduced the excitability of human DRG neurons, whereas a synthetic Vc1.1 analogue that is inactive at GABAB R did not. Human DRG neurons expressed GABAB R and its downstream effector channels CaV 2.2 and CaV 2.3. Mouse colonic DRG neurons exhibited high GABAB R, CaV 2.2 and CaV 2.3 expression, with upregulation of the CaV 2.2 exon-37a variant during CVH. Vc1.1 inhibited mouse colonic afferents ex vivo and nociceptive signalling of noxious CRD into the spinal cord in vivo, with greatest efficacy observed during CVH. A selective GABAB R antagonist prevented Vc1.1-induced inhibition, whereas blocking both CaV 2.2 and CaV 2.3 caused inhibition comparable with Vc1.1 alone. Conclusions: Vc1.1-mediated activation of GABAB R is a novel mechanism for reducing the excitability of human DRG neurons. Vc1.1-induced activation of GABAB R on the peripheral endings of colonic afferents reduces nociceptive signalling. The enhanced antinociceptive actions of Vc1.1 during CVH suggest it is a novel candidate for the treatment for CVP.